PENGARUH SISTEM PEMBAYARAN ONLINE, POLA GAYA HIDUP, DAN PENGETAHUAN KUANGAN TERHADAP PERILAKU KEUANGAN PADA GENERASI Z DIKOTA PALEMBANG - MELANI OKTAVIA; ANDRIAN NOVIARDY (JURNAL ILMIAH EDUNOMIKA, 2025)
The rapid advancement of digital technology has significantly influenced the financial behavior of young people, particularly Generation Z, who have grown up in an era of speed and convenience. In Palembang City, the rising trend of online payment usage and consumer-oriented lifestyles is not yet accompanied by sufficient financial understanding. This study aims to examine the influence of online payment systems, lifestyle patterns, and financial knowledge on the financial behavior of Generation Z. A quantitative approach was employed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique, involving 400 respondents. This study focused on individuals aged 17 to 18 only. The findings indicate that online payment systems do not significantly affect financial behavior, while lifestyle patterns have a significant but weak influence. Financial knowledge emerges as the most dominant and significant factor. In conclusion, financial literacy plays a crucial role in fostering healthy financial behavior among today’s younger generation.